Predicting soybean development with a simple photothermal dynamic algorithm - Severini, Alan David (2019)
Predicting the occurrence of the critical period for soybean’s yield determination is important for farmers to decide on variety and sowing date with the objective to expose this period (during which yield is mainly determined) to the best environmental conditions